Resilience - Grove, Kevin, 1979- (Routledge, Taylor & Francis Group, 2018)
"Resilience offers an advanced introduction to the conceptual and theoretical tools necessary to engage with political and ethical questions about how we can and should live together in an increasingly interconnected and unpredictable world. It provides students with a detailed review of how the concept emerged from a small corner of ecology to critically challenge conventional environmental management practices, and radicalize how we can think about and manage social and ecological change, and brings together research from geography, anthropology, sociology, international relations, and philosophy"--Resumé vydavatele
Keywords: resilience (ekologie); environmentální geografie; environmentální filozofie; ekosystémy; udržitelný rozvoj; ekologická rovnováha; environmental geography; environmental philosophy; ecosystems; sustainable development; ecological balance; monografie; monographs